Metronomic chemotherapy: bridging theory to clinical application in canine and feline oncology - Petrucci, Gonçalo N.; Magalhães, Tomás Rodrigues; Dias, Márcia; Queiroga, Felisbina Luísa (Frontiers in Veterinary Science, 2024)
Veterinary oncology has experienced significant evolution over the last few decades, with chemotherapy being currently applied to several neoplasms with therapeutic success. Traditionally, chemotherapy protocols are based on classic cytostatic drugs under the concept of maximum tolerated dose (MTD), which has been associated with a greater risk of toxicity and resistance. Thus, new therapeutic alternatives have emerged, such as metronomic chemotherapy (MC), introducing a new paradigm in cancer treatment. MC consists of administering low doses of chemotherapy drugs continuously over a long period of time, modulating the tumour microenvironment (TME) due to the combination of cytotoxic, antiangiogenic and immunomodulatory effects. This multi-targeted therapy has been described as a treatment option in several canine and feline cancers since 2007, with positive results already published in the literature, particularly in mammary carcinomas and soft tissue sarcomas Formatada: Português (Portugal) Formatada: Português (Portugal) Formatada: Tipo de letra predefinido do parágrafo Formatada: Não Realce Formatada: Justificado in dogs. The aim of this review article is to describe the current knowledge about the use of MC in small animal oncology, with emphasis on its mechanisms of action, the most commonly used drugs and clinical outcome.